Karateristik Komposit Serat Tandan Kosong Kelapa Sawit dengan Perekat Lateks Komposit pada Pembuatan Karpet - Soeherman, Giffary Pramafisi; Ningtyas, Kurnia Rimadhanti; Supriyanto, Supriyanto (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2025)
Increasing palm oil factory production has an impact on increasing the palm oil waste produced.  Palm oil mill waste can be classified into three types, namely solid waste, liquid waste and waste. Processing or utilization of empty palm oil bunches (EPOB) by palm oil mills (POM) is still very limited.  The chemical content of naturally derived plant materials such as lignin, cellulose, hemicellulose and other materials, these contents are potential materials for strengthening household products such as carpets. The characteristics of EPOB fiber is that it has short fibers between 3-8 cm. The binder used is composite latex made from concentrated latex. The aim of this research on the characteristics of palm oil empty fruit bunch (EPOB) fiber composites with composite latex adhesive in making carpets is to obtain an increase in tensile strength as a characteristic of EFB fibers with composite latex, to obtain an optimal composition between fiber volume and latex compound to improve the mechanical properties of the carpet; and Creating new materials from natural sources that are easily degradable and environmentally friendly. The research results showed that the optimal composition produced in worm carpet was Treatment A4 with a formulation of 250 g of EFB fiber with a breaking stress value of 1.1 N/mm2, elongation at break of 240%, and tear resistance of 6.1 kg/cm3.